Discourses as Resources: Active Literacy Practices and a Microculture of Rich Meaning Making in an Urban Elementary Classroom. (November 2015) - Paugh, Patricia
This microanalysis of an extended discussion in an urban classroom explores the context in which rich discourses interacted to develop and extend deeper forms of meaning making by elementary students. The analysis first situates the study in the literature on classroom cultures where dialogic interactions are encouraged; such cultures develop when students' intellectual work and agency as learners are valued. Next, a critical discourse analysis focuses on one classroom event as a microculture where a variety of discursive patterns are highlighted. This exemplar demonstrates that the teacher and the students utilized multiple linguistic moves to respond to each other. The teacher modeled serious regard for the ideas of others, but also retained her authority to push students to question assumptions or think more deeply. Her fourth grade students' interactions mirrored these moves, indicating confidence and agency. The analysis connects these languages and literacy practices to the high levels of student engagement, stamina, and critical participation identified over time in this teachers' classroom. The goal of the analysis is to argue that high academic expectations lie not in the standardization of practices that are most often touted in reform agendas, but in meaningful classroom teaching that honors the social, cultural, and linguistic resources of students. It also seeks to emphasize the rich and additive opportunities that this type of exchange of perspectives offers for complex intellectual work in urban classrooms; classrooms that are often subject to subtractive rhetoric from the reform movement.